Relationships between trypanosome infection measured by antigen detection enzyme immunoassays, anaemia and growth in trypanotolerant N'Dama cattle - Trail, J.C.M.; D'Ieteren, G.D.M.; Viviani, P.; Yangari, G.; Nantulya, V.M. (Elsevier, 1992)
Relationships were evaluated between trypanosome infection as measured by antigen detection enzyme immunoassays (antigen ELISA), anaemia as determined by average packed red cell volume (PCV), and animal performance as assessed by daily weight gain in 99 N'Dama cattle in Gabon exposed to natural tsetse challenge at 11.5 months of age and recorded 14 times over a 13 week period. Approximately half the animals were found to be infected for an average of five of the 14 times that they were examined: 38 percent with Trypanosoma congolense, 13 percent with Trypanosoma vivax and 49 percent with a mixed infection. Trypanosoma congolense infections had significant deterious effects on animal growth, while T. vivax infections did not. Animals found on several occasions to be infected T. congolence had significantly lower PCV values than those demonstrated to be infected on fewer occasions. No relationship was found between mean optical density (OD) values in antigen ELISA and PCV values. Animals capable of maintaining PCV values, even when antigene ELISA positive on a high number of occasions, grew at the same rate as uninfected animals. Animals that could not maintain PCV values when infected had poorer growth. Antigene ELISA has the potential to increase the efficiency of selection of trypanotolerant N'Dama cattle under tsetse challenge in the field, in three main ways. (1) Accurate identification of trypanosome species, especially in mixed species infections, clarifies relations between infection, anaemia, and animal performance. (2) Detection of animals antigenaemic without patent parasitaemia could allow individuals with superior ability to control trypanosome infection to be identified. (3) More accurate measurement of the proportion of time an animal is infected allows more accurate evaluation of its anaemia control capability.